CD57+ CD4 T Cells Underlie Belatacept‐Resistant Allograft Rejection. Issue 4 (14th January 2016) - Espinosa, J.; Herr, F.; Tharp, G.; Bosinger, S.; Song, M.; Farris, A. B.; George, R.; Cheeseman, J.; Stempora, L.; Townsend, R.; Durrbach, A.; Kirk, A. D.
Abstract : Belatacept is a B7‐specific fusion protein used to prevent allograft rejection by blocking T cell costimulation. Generally efficacious, it fails to prevent acute rejection in a sizable minority of patients. In experimental models, memory T cells mediate costimulation blockade–resistant rejection (CoBRR), but this remains undefined in humans. To explore relationships between individual patients' immune cell phenotypes and CoBRR, we studied patients receiving belatacept or conventional calcineurin inhibitor–based immunosuppression. We identified a population of CD57 + PD1 − CD4 T cells present prior to transplantation that correlated with CoBRR. Contrary to data recognizing CD57 as a marker of senescence on CD8 T cells, we discovered a nonsenescent, cytolytic phenotype associated with CD57 on CD4 T cells. Moreover, CD57 + CD4 T cells expressed high levels of adhesion molecules implicated in experimental CoBRR, were CD28 −, expressed a transcriptional phenotype broadly defining allograft rejection and were shown to be present in rejecting human kidney allografts. These data implicate CD57 + CD4 T cells in clinical CoBRR. If prospectively validated, this characteristic could identify patients at higher risk for acute rejection on belatacept‐based therapy. Abstract : The authors identify a population of CD57+PD1‐ CD4 T cells present in the peripheral blood prior to transplantation that may identify patients at a higher risk for acute rejection on belatacept‐based therapy. See Shabir et al's article onpage 1113, and Murakami and Riella's editorial onpage 1045 .